2021
DOI: 10.3389/fcomm.2021.779227
|View full text |Cite
|
Sign up to set email alerts
|

Translated Transcripts From Covert Recordings Used for Evidence in Court: Issues of Reliability

Abstract: Nation states increasingly apply electronic surveillance techniques to combat serious and organised crime after broadening and deepening their national security agendas. Covertly obtained recordings from telephone interception and listening devices of conversations related to suspected criminal activity in Languages Other Than English (LOTE) frequently contain jargon and/or code words. Community translators and interpreters are routinely called upon to transcribe intercepted conversations into English for evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 8 publications
0
15
0
Order By: Relevance
“…The starting point of the judiciary is often that all transcripts provided by the prosecution (whether in English or translation into English from a foreign language) are accurate and fit for purpose for trials (Gilbert, 2014), and from there the defense can attempt to create uncertainty in trials about the meaning alleged by the prosecution (González et al, 2012). Although, as mentioned before, the primary evidence is the audio and the transcript is secondary (Gilbert and Heydon, 2021), in reality, audio recordings are not necessarily played in court trials for practical reasons: if the audio is in English, reading the transcript is easier for the triers of fact to visualize the words, as opposed to listening to ephemeral sounds in the recording; and if the audio is in a foreign language, there is even less incentive to play it, since triers of fact will have to rely on the translation anyway. Either way, jurors rely heavily on the transcript, unless there is a particular point the prosecution or the defense attempt to make about the recording, in which case the audio may be played.…”
Section: Two-step Processmentioning
confidence: 95%
See 2 more Smart Citations
“…The starting point of the judiciary is often that all transcripts provided by the prosecution (whether in English or translation into English from a foreign language) are accurate and fit for purpose for trials (Gilbert, 2014), and from there the defense can attempt to create uncertainty in trials about the meaning alleged by the prosecution (González et al, 2012). Although, as mentioned before, the primary evidence is the audio and the transcript is secondary (Gilbert and Heydon, 2021), in reality, audio recordings are not necessarily played in court trials for practical reasons: if the audio is in English, reading the transcript is easier for the triers of fact to visualize the words, as opposed to listening to ephemeral sounds in the recording; and if the audio is in a foreign language, there is even less incentive to play it, since triers of fact will have to rely on the translation anyway. Either way, jurors rely heavily on the transcript, unless there is a particular point the prosecution or the defense attempt to make about the recording, in which case the audio may be played.…”
Section: Two-step Processmentioning
confidence: 95%
“…For investigative purposes, professional interpreters may be employed to listen to live or covertly recorded telephonic communications and asked to provide investigators with either the gist or a full interpretation of the exchanges under surveillance; they may also be asked to identify matters of interest or scour for specific items of information instructed by the investigator. For evidentiary purposes, although the actual recording is regarded as the primary evidence and the transcript as secondary (Gilbert and Heydon, 2021), triers of fact (i.e., judges and jurors) must rely on the translation into English of the original utterances in the audio to access the meaning of the exchanges spoken in a foreign language that they do not understand.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately both of these tasks are carried out according to procedures developed with poor understanding of relevant aspects of linguistic science (Fraser, 2021b). Even more unfortunately, valuable efforts of experts to document the resulting problems (Capus and Griebel, 2021;Gilbert and Heydon, 2021) and suggest viable solutions (Gonzáles et al, 2012;NAJIT, 2019) are so far having limited impact on general practice.…”
Section: Discussionmentioning
confidence: 99%
“…The first point to be made is that to the authors' knowledge, there is no international legal authority defining a profile for expert witnesses with expertise in translation. Indeed researchers analysing data collected during the observation of public court trials in the Australian state of Victoria have brought to light the fact that: "[p]olice officers often provide expert witness testimony to explain the meanings of terms and phrases contained in translated transcripts", and more worryingly still, "[e]xpert witness testimony in these circumstances is often delivered by monolingual police officers" (Gilbert and Heydon 2021). A study of 150 judgments of the High Courts of Justice of Spain by Guillén Nieto (2020), concluded that in none of the cases analysed were the services of an expert linguist called upon by the court.…”
Section: Courts Calling Upon Expert Witnesses Concerning a Translatio...mentioning
confidence: 99%